The State Urge to be Physically Active‐Questionnaire (SUPA‐Q): Development and validation of a state measure of activity urges in patients with eating disorders - Lina Amin; Georg Halbeisen; Karsten Braks; Thomas J. Huber; Georgios Paslakis (Brain and Behavior, 2023)
Abstract Objective Many people, including patients with eating disorders (EDs), experience an increased urge for physical activity. “Trait”‐like activity in patients with EDs is assessed by existing questionnaires, but there are few clinically validated assessments of a “state” urge to be physically active. Here, we developed and validated the State Urge to be Physically Active‐Questionnaire (SUPA‐Q). Methods After developing and piloting the items, N = 126 patients with EDs (mostly anorexia nervosa and bulimia nervosa) took part in our mixed‐longitudinal validation study with one primary assessment for all patients and a secondary assessment for a subsample of patients. Cronbach's α and split‐half‐methods served as measures of consistency and reliability. Correlations with other questionnaires were used to determine convergent and divergent validity, and confirmatory factor analysis was used for investigating factorial validity. We used paired‐samples t‐tests for repeated assessments to investigate change sensitivity. Results We found the SUPA‐Q to be highly consistent, and reliable and to demonstrate convergent, divergent, and factorial validity. The comparison of SUPA‐Q scores from repeated assessments within a subsample of patients demonstrated the questionnaire's change sensitivity, Cohen's d = 0.48. Moreover, an increase in SUPA‐Q scores was associated with a less positive mood, more anxiety, more body dissatisfaction, more tenseness, less feelings of control, and more stress. Discussion The newly developed SUPA‐Q may help to accentuate the necessity to evaluate and address the acute urge to engage in physical activity in patients with EDs in clinical practice and ultimately support tailoring treatments to patients’ unique symptom patterns. The questionnaire is available at https://doi.org/10.17605/OSF.IO/G2YBC.